2010
DOI: 10.2503/jjshs1.79.161
|View full text |Cite
|
Sign up to set email alerts
|

Light Condition Influences Rutin and Polyphenol Contents in Asparagus Spears in the Mother-fern Culture System during the Summer–Autumn Harvest

Abstract: We investigated the variation in rutin and total polyphenol contents in asparagus spears under different conditions of mother-fern culture. Rutin and polyphenol contents were highest at early spring harvest at all test sites. The contents gradually decreased during the harvest season. In particular, a considerable decrease was observed after the growth of mother ferns. The absorption of the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical was weaker in summer. Rutin content in the spears of plants grown outdoors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
(16 reference statements)
1
16
0
2
Order By: Relevance
“…Protodioscin content in the sample solution was determined using HPLC equipped with an ELSD. HPLC analysis was conducted using a Shimadzu LC9A system (Shimadzu Co., Kyoto, Japan) equipped with a Model 300S ELSD (M&S Instruments Inc., Osaka, Japan) and a Waters Sunfire C18 (4.6 × 250 mm) column (Nihon Waters K. K., Tokyo, Japan), according to the modified method described by Wang et al (2003) and Maeda et al (2010). The mobile phases consisted of 0.1% trifluoroacetic acid (A) and acetonitrile (B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protodioscin content in the sample solution was determined using HPLC equipped with an ELSD. HPLC analysis was conducted using a Shimadzu LC9A system (Shimadzu Co., Kyoto, Japan) equipped with a Model 300S ELSD (M&S Instruments Inc., Osaka, Japan) and a Waters Sunfire C18 (4.6 × 250 mm) column (Nihon Waters K. K., Tokyo, Japan), according to the modified method described by Wang et al (2003) and Maeda et al (2010). The mobile phases consisted of 0.1% trifluoroacetic acid (A) and acetonitrile (B).…”
Section: Methodsmentioning
confidence: 99%
“…Asparagus (Asparagus officinalis L.) is a popular vegetable in Japan (Kitazawa et al, 2011;Maeda et al, 2005Maeda et al, , 2010Maeda et al, , 2012. Although green asparagus is the commonly cultivated form in Japan, the consumption of fresh white asparagus has increased because of its pleasing taste.…”
Section: Introductionmentioning
confidence: 99%
“…The relations between light and rutin (flavonoids) have been studied well and reported that the rutin played a role as protector against ultraviolet (UV) in living plants (Kubasek et al, 1992;1998;Wade et al, 2001;Rozema et al, 2002;Ebizawa et al, 2008). In the mother-fern culture during summer to autumn harvest, by improved the light environment rutin content become significantly high (Maeda et al, 2010). Study in buckwheat showed that rutin getting higher according to the light such as UV-B specifically (Lee et al, 2001;Kreft et al, 2002;Li et al, 2010;.…”
Section: Discussionmentioning
confidence: 99%
“…최근 연구에 의하면 비가림 하우스에서 재배 된 아스파라거스 순은 폐암세포 증식 억제 효과 등이 보고되었 다 (Lee et al, 2015). 또한 아스파라거스 순은 인체 내의 콜레스 테롤을 줄이고 암 세포 활성 억제 (Chin and Garrison, 2008;Maeda et al, 2010;Shao et al, 1996;Shou et al, 2007 간 측정하여 H2O2산화를 측정하였다 (Chen and Asada, 1989).…”
unclassified